Preclinical evaluation and first in human study of Al18F radiolabeled ODAP-urea-based PSMA targeting ligand for PET imaging of prostate cancer - Ren, Ya’nan; Liu, Chen; Liu, Teli; Duan, Xiaojiang; Zhang, Qian; Liu, Jiayue; Wang, Pei; Guo, Qian; Yang, Xing; Du, Peng; Zhu, Hua; Yang, Zhi (Frontiers in Oncology, 2022)
Purpose: This study aimed to introduce a novel [18F]AlF-labeled ODAP-Urea-based Prostate-specifc membrane antigen (PSMA) probe, named [18F]AlF-PSMA-137, which was derived from the successful modification of glutamate-like functional group. The preclinically physical and biological characteristics of the probe were analyzed. Polit clinical PET/CT translation was performed to analyze its feasibility in clinical diagnosis of prostate cancer. Methods: [18F]AlF-PSMA-137 was maturely labeled with the [18F]AlF2+ labeling technique. It was analyzed by radio-HPLC for radiochemical purity and stability analysis in vitro and in vivo. The PSMA specificity was investigated in PSMA-positive (LNCaP) and PSMA-negative (PC3) cells, and the binding affinity was evaluated in LNCaP cells. Micro-PET/CT imaging was performed in mice bearing LNCaP or PC3 tumors. Thirteen patients with newly diagnosed prostate cancer were included for [18F]AlF-PSMA-137 PET/CT imaging. Physiologic biodistribution and tumor burden were semi-quantitatively evaluated and the radiation dosimetry of [18F]AlF-PSMA-137 was estimated. Results: The radiochemical yield of [18F]AlF-PSMA-137 was 54.2 ± 10.7 % (n = 16) with the radiochemical purity over 99% and the specific activity of 26.36 ± 7.33 GBq/μmol. The binding affinity to PSMA was 2.11 ± 0.63 nM. [18F]AlF-PSMA-137 showed high cell / tumor uptake which can be specifically blocked by PSMA inhibitor. According to the biodistribution in patients, [18F]AlF-PSMA-137 was mainly accumulated in kidneys, lacrimal glands, parotid glands, submandibular glands and liver which was similar to the extensive Glu-Ureas based probes. A total of 81 lesions were detected in PET/CT imaging and over 91% of lesions increased between 1 h p.i. (SUVmean: 10.98 ± 18.12) and 2 h p.i. (SUVmean: 14.25 ± 21.28) (p < 0.001). Additionally, the probe showed intensive accumulation in lesions which provided excellent imaging contrast with the high tumor-to-muscle ratio of 15.57 ± 27.21 at 1 h p.i. and 25.42 ± 36.60 at 2 h p.i. (p < 0.001), respectively. The effective dose of [18F]AlF-PSMA-137 was estimated as 0.0119±0.0009 mSv/MBq. Conclusion: An ODAP-Urea-based PSMA probe [18F]AlF-PSMA-137 was successfully prepared with high specificity and binding affinity to PSMA. Micro-PET/CT imaging study demonstrated its feasibility for prostate cancer imaging. Pilot clinical study showed its potential for delay-imaging and prostate cancer detection.